2015
DOI: 10.17660/actahortic.2015.1069.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Compost Tea Inputs and Application Methods on Protecting Tomato From Phytophthora Capsici

Abstract: Numerous challenges exist in organic tomato production, one of the largest being a lack of amendments that can effectively serve as crop nutrients or pest controls and still be considered organic. Compost is a recognized organic input, and a recent development is the use of compost tea in fertility and biocontrol applications. Aerobic compost tea (ACT) is produced by aerating compost and water and allowing microbial activity to increase over a few days. An investigation into the biocontrol and fertility effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The application of organic amendments is another approach to biocontrol. For P. capsici management, Nicol and Burlakoti [ 183 ] aerated compost and water and produced four aerobic compost teas. When tested in the glasshouse, the researchers concluded that if these products were drenched in potting mix before and after P. capsici inoculation, the disease progression was reduced by over 70%, with improved plant growth.…”
Section: Control Strategies Of the Major Soilborne Fungal/oomycete Di...mentioning
confidence: 99%
“…The application of organic amendments is another approach to biocontrol. For P. capsici management, Nicol and Burlakoti [ 183 ] aerated compost and water and produced four aerobic compost teas. When tested in the glasshouse, the researchers concluded that if these products were drenched in potting mix before and after P. capsici inoculation, the disease progression was reduced by over 70%, with improved plant growth.…”
Section: Control Strategies Of the Major Soilborne Fungal/oomycete Di...mentioning
confidence: 99%
“…It investigates the effects of different compost types on soil properties and nutrient availability, providing insights into compost application's potential benefits and limitations. At the same time, Nicol and Burlakoti [70] examine the effect of aerobic compost tea inputs and application methods on protecting tomato plants from Phytophthora capsici, a destructive plant pathogen. The study investigates the efficacy of compost tea in disease management, highlighting its potential as a sustainable alternative to chemical fungicides.…”
Section: Chapter Effects Referencementioning
confidence: 99%
“…Aplikasi serbuk limbah media tanam jamur tiram yang dicampurkan pada lubang tanam serta air rendamannya disiramkan setiap dua minggu sekali dapat menekan penyakit moler yang disebabkan Fusarium oxysporum f. sp cepae pada tanaman bawang merah sebesar 43,7-76,3% (Yusidah & Istifadah, 2018) dan juga menghambat perkembangan penyakit layu bakteri pada tanaman kentang (Istifadah & Sianipar, 2015). Nicol & Burlakoti (2015) juga melaporkan bahwa air rendaman limbah media jamur konsumsi menghambat pertumbuhan Phytophthora capsici secara in vitro dan penyakit hawar daun pada tanaman cabai. Kemampuan limbah media jamur ataupun air rendamannya dalam menekan penyakit tanaman pada umumnya karena adanya mikrob yang bersifat antagonistik terhadap patogen (Adedeji & Aduramigba, 2016;Goonani et al, 2011;Herawati & Istifadah, 2018).…”
Section: Pendahuluanunclassified